PSO based decentralized robust power system stabilizer for a multi-machine power system - Kaitwanidvilai, Somyot; Ussawapusitgul, Chanchai; Limcharoen, Worrakan (My University, 2012)
This paper presents a new technique to design a robust Power System Stabilizer (PSS) in multi-machine power system. The Particle Swarm Optimization (PSO) is adopted to find the optimal parameters of the predefined structure decentralized controller. The main objectives of this research are to reduce the oscillation and to increase the overall robust performance of the system. The proposed technique adopts the stability margin (ε) as the index of robustness and performance of the controlled system. In addition, the optimal weight selection, which is a difficult process of the robust loop shaping design, can be achieved by the proposed technique. In this paper, the performance of the proposed controller is investigated in the standard IEEE four generators system in comparison with the classical robust loop shaping control. The results of rotor speed deviation of generators by the proposed PSS and the conventional PSS verify the effectiveness of the proposed algorithm.
Keywords: Eigen value; Inter-area oscillation; Particle swarm optimization; Power system stabilizers